A review of HIV and AIDS curricular responses in the higher education Sector: Where are we now and what next? - Wood, L.; Pillay, M. (South African Journal of Higher Education, 2016)
Curriculum integration of HIV and AIDS in higher education is a strategic priority of the Higher Education AIDS programme (HEAIDS), yet little progress has been made in this area. To address this, HEAIDS is leading a project aimed at capacitating the development of HIV curriculum initiatives. The purpose of this article is to present a critical overview of internationally published work concerning the integration of HIV and AIDS into the curriculum of higher education, to determine what has been done in terms of integration, to assess what has been evaluated as successful, and to determine what lessons we can draw from it to inform the way forward. A total of 106 sources were identified by conducting key word searches in three main search engines; additional references from these and back issues of leading HIV and AIDS education journals were also consulted. We critically discuss the findings to draw conclusions about best practices concerning theoretical underpinnings, pedagogy and curriculum content. We conclude by highlighting some aspects that can help to inform the infusion of HIV and AIDS into the curricula of higher education in South Africa and beyond.